Multidisciplinary team of intensive therapy: humanization and fragmentation of the work process - Evangelista, Viviane Canhizares [UNESP]; Domingos, Thiago da Silva [UNESP]; Cerantola Siqueira, Fernanda Paula; Braga, Eliana Mara [UNESP] (Assoc Brasileira Enfermagem, 2016)
Objective: to understand the meaning of humanized care in intensive care units considering the experience of the multidisciplinary team. Method: descriptive and exploratory qualitative research. For this purpose, we conducted semi-structured interviews with 24 professionals of the heath-care team, and, after transcription, we organized the qualitative data according to content analysis. Results: from two main categories, we were able to understand that humanized care is characterized in the actions of health-care: effective communication, team work, empathy, singularity, and integrality; and mischaracterized in the management processes, specifically in the fragmentation of the work process and health-care, in the precarious work conditions, and in differing conceptual aspects of the political proposal of humanization. Conclusion: care activities in intensive therapy are guided by the humanization of care and corroborate the hospital management as a challenge to be overcome to boost advances in the operationalization of this Brazilian policy.
Keywords: Care Humanization; Critical Care; Health Team; Health Management; Work Conditions